Short term regulation of acyl CoA: Cholesterol acyl transferase (ACAT) activity in the regenerating and perinatal liver. Issue 3 (March 1985) - Bruscalupi, G.; Leoni, S.; Mangiantini, M. T.; Piemonte, F.; Spagnuolo, S.; Trentalance, A.
Abstract : Acyl coenzyme A:cholesterol acyltransferase (ACAT), the enzyme catalyzing the hepatic cholesterol esterification could be involved in the modified availability of cholesterol detectable in proliferating systems. While no significant variations are detectable in the regenerating liver, the modified ACAT activity during liver development and its differential sensitivity to the in vitro stimulation of modulatory systems suggest an involvement of the enzyme in this proliferating process.